Bile: miRNA pattern and protein-based biomarkers may predict acute cellular rejection after liver transplantation. (2nd January 2017) - Schmuck, Rosa Bianca; Reutzel-Selke, Anja; Raschzok, Nathanael; Morgul, Haluk Mehmet; Struecker, Benjamin; Lippert, Steffen; de Carvalho Fischer, Cynthia; Schmelzle, Moritz; Boas-Knoop, Sabine; Bahra, Marcus; Pascher, Andreas; Pratschke, Johann; et al.
Abstract: Context: Bile rather than blood depicts the local inflammation in the liver and may improve prediction and diagnosis of acute cellular rejection (ACR) after liver transplantation (OLT). Methods: Secretome and miRNAs were analyzed during the first two weeks and on clinical suspicion of ACR in the bile of 45 OLT recipients. Results: Levels of CD44, CXCL9, miR-122, miR-133a, miR-148a and miR-194 were significantly higher in bile of patients who developed ACR within the first 6 months after OLT and during ACR. Conclusion: Analysis of secretome and miRNA in bile could improve our understanding of the local inflammatory process during rejection.